Cache privacy protection strategy in content centric networking - Yi ZHU; Zheng-kun MI; Wen-nai WANG (Tongxin xuebao)
Cache privacy leak was one of the important security threats of CCN,the adversary could obtain the legitimate user’s privacy information through probing cache visiting time.Aiming at this security problem,the privacy and non-privacy contents were dealt separately,then a cache privacy protection strategy based on recent visiting information and evicted copy up (CPPS-RVI＆amp;ECP) was proposed.In order to compare with the current typical defense strategy-random first k delay (RFKD),the theoretical analysis of privacy leak probability and network hit probability are further given.The CPPS-RVI＆amp;ECP identifies the recent visitor by setting privacy mark in interest packet,decreases the privacy leak probability by selecting replacing position randomly,and promotes the network performance by the mechanism of shifting evicted copy upstream.The numeric analysis results under the prescribed experimental conditions show that,whereas the ideal privacy protection ability of RFKD is obtained at the expense of sacrifice of cache contents delivery capability,the proposed CPPS-RVI＆amp;ECP can obtain low privacy leak probability and in the meantime maintain high network hit probability by setting reasonable upstream shifting probability.